eHealth - information seeking behaviour among school going adolescents through internet - Thakan, Somya; Mehta, Aditya; Singh, Lakhan (International Journal Of Community Medicine And Public Health, 2022)
Background: Health literacy implies the achievement of a level of knowledge, personal skills, and confidence to take action to improve personal and community health by changing personal lifestyles and living conditions. Thus, health literacy means more than being able to read pamphlets and make appointments. Poor literacy can affect people’s health directly by limiting their personal, social, and cultural development, as well as hindering the development of health literacy. Methods: Analytical cross-sectional study was conducted among school-going adolescents. From six in-depth interviews and a brief paper-and-pencil questionnaire with seventy-nine adolescents. These adolescents were primarily presented with and fulfilled nutrition information needs informal settings such as school. Results: Average age of school-going adolescents was 12.67 years with a majority of 96% having internet access. The majority of them had sought the help of the internet to gather nutrition information. Conclusions: Overall, for these adolescents, the nutrition information-seeking process was not an engaging, iterative process. Their nutrition information-seeking behaviours indicated that these adolescents were only at a basic level finding and making sense of nutrition information.